PERFORMANCE OPTIMIZATION THROUGH LEARNING MANAGEMENT SYSTEM - Dedy Eko Widianto; Kiki Farida Ferine (Universitas Efarina, 2025)
This study aims to analyze the effect of Ability and Skills and Motivation on Employee Performance with Learning Management System – My Learning as an intervening variable at PT iForte Solusi Infotek West Region. The population of this study consisted of all employees at PT iForte Solusi Infotek West Region, with a total of 110 respondents selected using a saturated sampling method. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Ability and Skills have a positive and significant effect on Employee Performance, and also significantly influence the use of Learning Management System – My Learning. Motivation has a positive and significant effect on the use of the Learning Management System but does not directly affect Employee Performance. Furthermore, Learning Management System – My Learning significantly mediates the relationship between both Ability and Skills and Motivation with Employee Performance. The R² value for Employee Performance is 0.769, indicating that 76.9% of the variance in performance can be explained by the variables in the model, while 87.2% of the variance in LMS usage is explained by Ability and Skills and Motivation. This study concludes that developing employees' abilities, skills, and motivation through Learning Management System – My Learning is an effective strategy to improve employee performance. The findings provide important implications for companies in designing training programs and managing digital learning systems.